Five new species of Nealcidion Monné, 1997 from Ecuador (Coleoptera, Cerambycidae, Lamiinae) - Vlasak, Josef; Santos-Silva, Antonio (Zootaxa, 2022)
Five new species of Nealcidion Monné, 1997 are described from Ecuador: Nealcidion obliquum sp. nov., Nealcidion flavoviride sp. nov., Nealcidion cephaliferum sp. nov., Nealcidion sublineatum sp. nov., and Nealcidion calcaratum sp. nov. All new species are illustrated, making it easier to recognize the species and to follow the descriptions.